204k views
3 votes
X² + 4x + 3
How is this solved step by step it needs to be in factored form

User Elynch
by
5.7k points

2 Answers

0 votes

Answer:


\large\boxed{x^2+4x+3=(x+3)(x+1)}

Explanation:


x^2+4x+3\\\\\text{We are looking for a and b, for which a + b = 4 and (a)(b) = 3}\\\\\text{a=3,\ b=1}\\\\=x^2+3x+1x+3\qquad\text{use the distributive property:}\ a(b+c)=ab+ac\\\\=x\underbrace{(x+3)}_((*))+1\underbrace{(x+3)}_((*))\qquad\text{use the distributive property}\\\\=\underbrace{(x+3)}_((*))(x+1)

User Jsalvador
by
4.3k points
3 votes
Do c=b meaning that you need to number that multiply to c but the sum of those numbers give u the value of b. The answer would be (x+3)(x+1) because both are positive.
User Kousen
by
4.7k points